Ømålsordbogens beskrivelse af verbalbøjning - Gudiksen, Asgerd (Nordiske Studier i Leksikografi, 2012)
The article presents and discusses the lexicographical description of conjugation in Ømålsordbogen (The Dictionary of the Insular Dialects). Ømålsordbogen describes the traditional dialects with 1850–1945 as its core period. The source materials are mainly records collected from about 1920 to about 1940, often unique information not to be found elsewhere. However, only a minor number of verbs have been recorded systematically. Consequently, the morphological data of a verb are often incomplete and therefore difficult to interpret and describe. Another challenge for the dialect lexicographer is to account for the inflectional variation that may be both geographical and chronological, without making the microstructure too difficult to access.